OP0114 Interim Safety and Efficacy Results of Patients with Cryopyrin-Associated Periodic Syndrome Participating in the β-Confident Registry. (10th June 2014) - Kuemmerle-Deschner, J.B.; Tilson, H.H.; Hawkins, P.N.; van der Poll, T.; Walker, U.A.; Abrams, K.; Hoffman, H.M.
Abstract : Background: Cryopyrin-associated periodic syndrome (CAPS) is a continuum of rare hereditary disorders that includes three phenotypes, in the order of severity: familial cold auto-inflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and chronic infantile neurologic cutaneous and articular syndrome/neonatal onset multisystem inflammatory disease (CINCA/NOMID). 1 Here we present the current safety data of canakinumab (CAN) use in CAPS patients (pts) in clinical practice from the on-going observational β-Confident Registry, involving 40 sites in 13 countries in EU region and US. Objectives: To monitor and explore the overall safety of CAN with a focus on serious adverse events (SAEs), including serious infections, vertigo, malignancies and hypersensitivity reactions. The secondary objective is to measure efficacy using physician's global assessments (PGA). Methods: β–Confident Registry protocol does not mandate any visits or procedures, but records all observed and reported adverse events (AEs) and SAEs or AEs potentially related to treatment with CAN. Cumulative safety data are reported as incidence rate (number of events) per 100 patient-years (IR/100 pyr) from the date of first pt enrollment (19 November 2009) until the current data cut-off date (31 December 2013). Additional safety data will be updated, as available, at the time of the conference. Results: 270 pts were enrolled with a mean duration of 154 weeks (2-233 weeks) in the registry. In total 4 (1.5%) pts discontinued CAN due to an AE and 5 (1.9%) due to poor efficacy. The most common types of AEs (IR >2/100 pyr) are reported in the table below. Pts with FCAS, the least severe phenotype, had the lowest AE incidence rate (44/100 pyr) as compared with pts with MWS (112/100 pyr) and NOMID (140/100 pyr), the more severe phenotypes. No hypersensitivity to CAN was reported as AEs. A total of 71 SAEs were reported by 42 pts (13.2 SAEs/100 pyr). The most common type of SAE was infection (3.2/100 pyr). One death in 76 yr MWS pt with metastatic rectal adenocarcinoma was reported. Of 8 (2.9%) pts that received pneumococcal vaccination (PPV), 7 reported a local post-PPV injection site reaction, 3 of which were considered serious. At the end of current data cut-off, based on PGA assessment, nearly half the pts had no disease activity while most others had mild/moderate disease activity. There was no evidence of loss of effect with time. Conclusions: The safety profile observed in the canakinumab CAPS registry is consistent with that observed in the clinical trial program. Response rates were as expected based on clinical trial experience with no evidence of loss of efficacy. References: Farasat S et al. Arch Dermatol. 2008;144:392-402 Disclosure of Interest: J. Kuemmerle-Deschner Grant/research support: Novartis, Consultant for: Novartis, H. Tilson Consultant for: Novartis on the Beta-Confident Registry (Chair) and 2 other Registry projects, P. Hawkins: None declared, T. van der Poll: None declared, U. Walker Consultant for: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, H. Hoffman Consultant for: Novartis. Also on an international registry committee for Novartis DOI: 10.1136/annrheumdis-2014-eular.3512